Computer applications in libraries and information centers in Metro Manila and librarian`s attitude toward computerization a survey - Lou Delong
This survey looks into the status of computer applications in the libraries and information centers in Metro Manila and the librarians' attitude toward computerization. Two hundred and twenty three libraries and information centers surveyed, which described the current status and the potentials of computer applications in libraries and information centers in Metro Manila as well as 74 professional librarians' attitudes toward library automation.